It Matters! Engage. Participate. Vote.: Is the Constitution Under Attack? - Sonoma State University Library (Sonoma State University)
Moderated by the Political Science Department, this annual event celebrates the US constitution. This year we will ask the question "Is the Constitution under attack?" A panel of speakers includes faculty members Eric Williams, Criminology and Criminal Justice, and Richard Hertz, Political Science. This discussion was held in the University Library, Jean & Charles Schulz Information Center on the SSU campus.